Correlating light-induced deep defects and phase segregation in mixed-halide perovskites. Issue 36 (1st September 2022) - Ridzoňová, Katarína; Grill, Roman; Peter Amalathas, Amalraj; Dzurňák, Branislav; Neykova, Neda; Horák, Lukáš; Fiala, Peter; Chin, Xin Yu; Wolff, Christian M.; Jeangros, Quentin; Holovský, Jakub
Abstract : The correlation between rate of light-induced phase segregation and deep defect formation observed in mixed-halide perovskites. The importance of grain size in determining the rate and terminal phase of segregation was highlighted. Abstract : Mixed-halide perovskites are highly promising materials for tandem solar cells. The phenomenon of phase segregation, however hinders their application. Here, we combine Fourier-Transform photocurrent spectroscopy with photoluminescence and current density–voltage ( J – V ) measurements to study the effect of light soaking on such materials and devices. At first, we observe a gradual formation of an I-rich phase, which correlates with an increase in deep defect level concentration. We attribute these deep defects to charged iodide interstitials and associate phase segregation with iodide migration through interstitial positions. Upon further light soaking, the second less I-rich phase forms, while the deep level concentration simultaneously decreases. An empirical model describing the phase segregation mechanism is proposed to rationalize these observations. Further, we point to an important role of grain size in determining the degree and terminal phase of segregation.